Children's literature in the classroom engaging lifelong readers - Barone, Diane M. (Solving problems in the teaching of literacy, 2011)
"This guide provides a wealth of ideas for incorporating high-quality children's books of all kinds into K-6 classrooms. Numerous practical strategies are presented for engaging students with picture books, fiction, nonfiction, and nontraditional texts."--Publisher's description.